Parameters Optimization for Manufacturing Advanced Self-Reinforced Composites based on Ultra-High Molecular Weight Polyethylene (Fracture and Structural Integrity, 2025)
In this study, the relationships between processing, structure and properties of self-reinforced ultra-high molecular weight polyethylene (UHMWPE) composites fabricated via thermal pressing are investigated. By systematically varying processing temperatures (145, 155, 165, 170, 175,180 °C) and pressures (25 and 50 MPa), we demonstrate that mechanical performance is governed by the interplay between fiber consolidation and the preservation of the oriented crystalline phase. Scanning electron microscopy reveals the presence of residual voids that are independent of the processing parameters, and which lead to interfacial failure and fibrillar fracture morphologies. We identify a critical processing threshold at 165 °C (25 MPa), which yields peak interlayer shear strength (7.8–11.1 MPa), bending strength (102–130 MPa), elastic modulus (23–42 GPa), and Charpy impact resistance (72–95 kJ/m²). Beyond this threshold, however, mechanical performance deteriorates due to fiber remelting and loss of anisotropy, resulting in the composite transitioning to an isotropic UHMWPE matrix. Conversely, elevated pressures fail to improve properties due to insufficient macromolecular interdiffusion, which is the dominant bonding mechanism. These findings establish a processing-structure-property framework for UHMWPE-based self-reinforced composites that balances interfacial adhesion and crystalline alignment, while providing actionable guidelines for engineering high-performance single-polymer materials.
Keywords: Self-reinforced composite (SRC); Ultra-high molecular weight polyethylene (UHMWPE); Scanning electron microscopy (SEM); interlayer shear test; Charpy impact test; bending; tension